The taxonomical aspect of Argostemma Wall. (Rubiaceae-Rubioidae) in Mount Gede- Pangrango, Mount Halimun, and Mount Salak based on morphological characteristics (Biodiversitas Journal of Biological Diversity, 2016)
Vegetative character and reproductive at Argostemma from Mount Gede-Pangrango, Mount Halimun, and Mount Salak have been used for the identification of 101 herbarium specimens from Herbarium Bogoriense and new specimens from field. Identifying of herbarium specimens based morphology character on Argostemma hybrid group by previous author still identified as Argostemma montanum. Ovary at Argostemma consist of 2-3 celled, ovary 2 celled is found at A. montanum and A. borragineum, while the ovary of A. uniflorum account of3 celled. Amount of flower do not range from 3-6, but between 1-8. Study on Argostemma morphology also can be concluded that in Mount Gede-Pangrango, Mount Halimun, and Mount Salak there are 3 Argostemma species, that is A. montanum Blume ex DC, A. borragineum Blume ex DC, and A. uniflorum Blume ex DC. Spreading of Argostemma vertically in Mount Gede-Pangrango, Mount Halimun, and Mount Salak range from 560-2,600 m above sea level. with spreading center 1,000-2,000 m above sea level.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: Argostemma, morphological characteristics, herbarium specimens, Mount Gede-Pangrango, Mount Halimun, Mount Salak.